Implementation of Integrated Information System in Optimization of Public Services in The Regional Revenue Agency of Deli Serdang - Nurhasanah Febriyanti Harahap; Rizka Khairunnisya Br Sinaga; Amelia Amelia; Siti Nurhaliza; Nurul Nazwa Ayu Malinda; Adrial Falahi; Mhd Dani Habra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the implementation of an integrated information system in public services at the Regional Revenue Agency (Bapenda) of Deli Serdang, particularly in the process of managing regional taxes. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the study show that the implementation of the integrated information system provides significant benefits in improving service efficiency, transparency, and taxpayer compliance. However, several challenges such as public digital literacy, data security, and resistance to change remain obstacles in its implementation. Therefore, solutions such as education, strengthening cybersecurity, and human resource training need to be applied to ensure the sustainability of this system. With continuous development, the integrated information system is expected to enhance the effectiveness of government administration and overall community welfare. The integrated information system implemented at Bapenda Deli Serdang also provides various conveniences, including integration with banks and financial institutions that accelerate the tax payment process and allow for real-time monitoring and evaluation of tax revenues. Additionally, the available digital public information services make it easier for the public to access information related to taxes and levies in a more transparent manner. Thus, the application of technology in this system not only increases efficiency but also contributes to improved tax compliance and the optimization of regional revenue.